Ask a question

consider the equations: f(x)= -6x-1 and g(x) =4x^2 what is the solution for (f+g)(x)?

Learning functions, need help with some word problems.

3 Answers by Expert Tutors

Tutors, sign in to answer this question.
Wael I. | Mathematics and Arabic LanguageMathematics and Arabic Language
(f+g)(x) = f(x) + g(x)
(f+g)(x) = -6*x - 1 + 4*x^2
(f+g)(x) =4x^2 - 6x -1
if you mean (f o g)(x)
if so
( f o g)(x) = f (g(x)) 
( f o g)(x) = f (4x^2)*******[g(x) = 4*x^2, so i just substitute it]
f(x)= -6x-1 , now just substitute the value of x with 4x^2
f(4x^2)= -6*(4x^2)-1
f(4x^2)= -24x^2-1
( f o g)(x) = -24x^2-1
Jada T. | Math, Economics, Business, GRE, ACT, ChickenologyMath, Economics, Business, GRE, ACT, Chi...
What it is saying is add the functions together and that they are both functions of x. This is an order of operations problem. If it had said f(g(x)) Then the g function would go in place of the x's in the f function. -6(4x^2)-1. However what you are asking is for (f+g)(x)
So for this problem:
(f+g)(x)= -6x-1+4x^2
I'm not sure if you need to solve for x. If so you will need to use the quadratic formula.
Christopher D. | Mathematician and ProgrammerMathematician and Programmer
4.9 4.9 (297 lesson ratings) (297)
(f+g)(x) = f(x) + g(x) = 4x2 - 6x - 1. This is quadratic, you can solve by using the quadratic formula. (Remember that "solving" a function means to find its zeros; i.e. when does f(x) = 0.)